2012
DOI: 10.1016/j.tmaid.2011.12.003
|View full text |Cite
|
Sign up to set email alerts
|

A model-based tool to predict the propagation of infectious disease via airports

Abstract: Epidemics of novel or re-emerging infectious diseases have quickly spread globally via air travel, as highlighted by pandemic H1N1 influenza in 2009 (pH1N1). Federal, state, and local public health responders must be able to plan for and respond to these events at aviation points of entry. The emergence of a novel influenza virus and its spread to the United States were simulated for February 2009 from 55 international metropolitan areas using three basic reproduction numbers (R(0)): 1.53, 1.70, and 1.90. Empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…OAG is an air travel intelligence company which has a large network of air travel data, also available for purchase (OAG). [1,2,3,4,5,6,7,10,11,12,14,16,17,18,19,20,22,23,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,48,50,51,52,53…”
Section: Identified Datasetsmentioning
confidence: 99%
“…OAG is an air travel intelligence company which has a large network of air travel data, also available for purchase (OAG). [1,2,3,4,5,6,7,10,11,12,14,16,17,18,19,20,22,23,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,48,50,51,52,53…”
Section: Identified Datasetsmentioning
confidence: 99%
“…In this study, the values reported by the WHO and Korea's census data with respect to outbreak of the H1N1 influenza pandemic in 2009 were applied to parameters. Additionally, the number of contactable individuals per patient, that is, 1.53 was obtained from the data on the outbreak of the 2009 influenza virus; this was adopted for reproduction value [14]. In cases of additional parameter values, 2 days were applied to latent incubation time, 0.95 to percentage of immunized agents, 0.9 to percentage of recovered agents, 0.14 to percentage of dead agents, 5 days to minimum time of dead agents, 14 days to maximum time to be recovered, and lastly, Korea census data were referred to for total population size.…”
Section: Epidemiological System Dynamics Modelingmentioning
confidence: 99%
“…The initial time of the infectious disease introduction to the country was based on the patterns of aerial network and dynamic characteristics of infectious disease. The infection rate and location where the disease was first observed were predicted [14].…”
Section: Introductionmentioning
confidence: 99%
“…These can be large cities and hubs of international air travel, or more localized border areas with high rates of ground travel between nations. [2][3][4][5] Hepatitis A is no exception. Recent evidence suggests that hepatitis A cases in the United States are primarily exposed when traveling outside of the United States and Canada.…”
Section: Introductionmentioning
confidence: 99%